Are National Curriculum objectives for teaching English being met in Icelandic compulsory schools? - Samuel C. Lefever 1954- (2009)
This article looks at recent research on English language teaching at the compulsory level in Iceland with regard to National Curriculum objectives. Three main issues are discussed: types of teaching methods used, the use of English during instruction, and the types of assessment methods used. The National Curriculum for foreign languages follows the principles of communicative language teaching and emphasizes the teaching of all four skills (reading, listening, writing and speaking)and integrating grammar and vocabulary with skills-based instruction. Teachers are encouraged to use a variety of techniques, activities, and materials that take into account diverse learning needs, use English as much as possible during instruction, and assist students in becoming autonomous learners through goal-setting and self-assessment. Assessment should be constructive, informative and include a variety of methods. Formal assessment (written tests) is not considered appropriate for learners in grades 1-5. An analysis of studies of English teaching at the compulsory level shows a discrepancy between communicative teaching methods recommended by the National Curriculum and those used in English instruction. Traditional methods of teaching and assessment are predominately used in schools. On the whole, instruction is teacher-directed and text-book bound and innovative approaches towards more holistic, learner-centered teaching do not seem to have gained ground. Teachers are not fulfilling their role of using English for classroom interaction and communication, and students are not provided with ample opportunities for authentic and creative use of English. Finally, traditional assessment methods based on written tests are used by most teachers, particularly in the upper grades, and little progress has been made in introducing alternative assessment methods recommended by the National Curriculum